Genetic variants of methionine metabolism and DNA methylation. (December 2014) - Bleich, Stefan; Semmler, Alexander; Frieling, Helge; Thumfart, L; Muschler, Marc; Hillemacher, Thomas; Kornhuber, Johannes; Kallweit, Ulf; Simon, Matthias; Linnebank, Michael
Aim: Altered DNA methylation is associated with important and common pathologies such as cancer. The origin of altered DNA methylation is unknown. The methyl groups for DNA methylation are provided by methionine metabolism. This metabolism is characterized by a high interindividual variability, which is in part explained by genetic variants.Methods: In a cohort of 313 individuals derived from a family-based study with index cases of cerebrovascular disease, we analyzed whether global methylation of leukocyte DNA was associated with age, gender, homocysteine plasma levels or functionally relevant genetic variants.Results: We observed an association of the G-allele of the methionine synthase variant c.2756A>G (D919G) with global methylation (% methylation ± 1 SD, AA: 41.3 ± 14.9; AG: 36.4 ± 18.2; GG: 30.8 ± 16.9; F = 4.799; p = 0.009). The methionine synthase variant c.2756A>G is associated with various types of cancer.Conclusion: Our data suggest that an impact on DNA methylation may contribute to the clinical relevance of the methionine synthase variant.